Use of dimensionless time and water volume to estimate subsurface drip irrigation wetted zone in different soil textures - Ali Shabani; Ali Reza Sepaskhah; Mohammad Golestani; Vahid Shahabi Zad (Scientific Reports)
Abstract Accurate estimation of the geometric characteristics of the wetted zone, including depth, height, and width, is crucial for optimizing subsurface drip irrigation (SDI) system design and management. This study evaluated and compared two dimensionless analysis models—based on dimensionless time and dimensionless water volume—for predicting the wetted zone parameters in three soil textures: sandy loam, loam, and clay loam. The dimensionless time-based (DTB) model incorporated parameters such as initial soil water content (ISWC), dripper flow rate, and alpha value (the reciprocal of the macroscopic length scale in hydraulic conductivity function), while the dimensionless water volume-based (DWVB) model used ISWC, saturated hydraulic conductivity, dripper flow rate, and installation depth. Experimental data were collected using a glass box setup with varying soil textures, dripper flow rates, and different ISWC conditions. Statistical indices, including NRMSE, MRE, EF, and R², were used to assess model performance. Results indicated that the DTB model outperforms the DWVB model, demonstrating higher accuracy in predicting wetted zone dimensions across all soil types. The study highlighted the influence of soil texture on water movement, with finer-textured soils exhibiting greater lateral spread due to higher matric suction, while coarser soils showed deeper vertical infiltration. The findings provided valuable insights for improving SDI system design and management, particularly in diverse soil conditions.